PENGARUH SALURAN DISTRIBUSI DAN HARGA DISKRIMINASI TERHADAP VOLUME PENJUALAN PADAPT. PRESOL INDO PRIMA PALEMBANG( Studi Kasus) - Irawan, Benny (Jurnal Manajemen, 2019)
This study aims to determine how the influence of distribution channels and discrimination price to the volume of sales at PT. Presol Indo Prima Palembang. The study was conducted by questionnaire which contains the revelation open to al l agents of the distribution system and price the data distribution obtained 52 respondents. Data analyzing using multiple regression analysis with SPSS version17. The results showed that the distribution channel and discrimination price significantly affect the sales volume amounted to (97.4%) and (86,4%) Thus, it can be concluded that there is significant influence and positive relationship between the distribution channels and discrimination price to the volume of sales at PT. Presol Indo Prima Palembang.